Use of Proton Pump Inhibitors and risk of gastric cancer - Tarkan Karakan (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Karakan T. Use of Proton Pump Inhibitors and risk of gastric cancer. Turk J Gastroenterol 2018; 29: 139-40.